DIAGNOSIS OF DISEASES USING ARTIFICIAL INTELLIGENCE IN ORTHOPEDIC DENTISTRY - Normurodova R. Z.-; Safarov M.T. (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Artificial intelligence is a rapidly developing technology that is increasingly being implemented in the life of modern people. One of the promising areas of its application is dentistry. Modern technologies allow the use of artificial intelligence to improve the effectiveness of diagnosis, treatment and prevention of oral diseases. The use of artificial intelligence in dentistry allows doctors to work more efficiently and accurately. In addition, the use of modern technologies accelerates the treatment process, makes it more comfortable for patients and improves the quality of the results obtained. This article discusses the areas of application of artificial intelligence, its advantages and disadvantages. Methods and technologies that contribute to optimizing the processes of diagnosis, treatment and prevention were analyzed. New technologies can dramatically change the healthcare system, improving the quality of services while reducing costs for clinics. In the future, the use of artificial intelligence will become an integral part of dental practice, which will allow achieving maximum results in the diagnosis, treatment and prevention of oral diseases.